2017
DOI: 10.1016/j.stemcr.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of LGR5 Expression Inhibits Cardiomyocyte Differentiation and Potentiates Endothelial Differentiation from Human Pluripotent Stem Cells

Abstract: SummaryUnderstanding molecules involved in differentiation of human pluripotent stem cells (hPSCs) into cardiomyocytes and endothelial cells is important in advancing hPSCs for cell therapy and drug testing. Here, we report that LGR5, a leucine-rich repeat-containing G-protein-coupled receptor, plays a critical role in hPSC differentiation into cardiomyocytes and endothelial cells. LGR5 expression was transiently upregulated during the early stage of cardiomyocyte differentiation, and knockdown of LGR5 resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
4
9
0
Order By: Relevance
“…Collectively, LGR5 functions as a growth-promoting molecule and promotes cellular proliferation of several stem cells in various organs and tissues (Barker and Clevers, 2010). LGR5 appears to play a central role in Wnt signaling, as it has been previously reported that LGR5 knockdown inhibited cellular proliferation of early differentiating cells and decreased the expression of Wnt signaling-related genes and nuclear-localized active b-catenin (Jha et al, 2017). This was further validated in our study, where LGR5 deletion decreased the expression of another Wnt activator (transcription factor) LEF1 and also blocked the LEF1's binding on the human-specific ISL1 promoter region.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Collectively, LGR5 functions as a growth-promoting molecule and promotes cellular proliferation of several stem cells in various organs and tissues (Barker and Clevers, 2010). LGR5 appears to play a central role in Wnt signaling, as it has been previously reported that LGR5 knockdown inhibited cellular proliferation of early differentiating cells and decreased the expression of Wnt signaling-related genes and nuclear-localized active b-catenin (Jha et al, 2017). This was further validated in our study, where LGR5 deletion decreased the expression of another Wnt activator (transcription factor) LEF1 and also blocked the LEF1's binding on the human-specific ISL1 promoter region.…”
Section: Discussionsupporting
confidence: 86%
“…This was further validated in our study, where LGR5 deletion decreased the expression of another Wnt activator (transcription factor) LEF1 and also blocked the LEF1's binding on the human-specific ISL1 promoter region. Although LGR5 has not previously been considered as having any relation to or causative roles in mammalian cardiogenesis, we demonstrated that LGR5 is required for CM induction through expansion of the ISL1 + TNNT2 + intermediates via human-specific transcriptional interactions such as MESP1-LGR5 and LEF1-ISL1 in vitro, which is partly supported by the latest report from another lab (Jha et al, 2017). One limitation in the current study is that it has not been fully addressed what the unique molecular identity of LGR5 + CPCs is, compared to LGR5 À CPCs, and what molecular cue drives LGR5 + CPCs to become CMs more favorably (Figure 2I), although the in vitro gene expression analysis showed that early cardiogenic and second heart field-related genes were enriched in LGR5 + cells than in LGR5 À cells (Figures 3F and 3G).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Additionally, GINS3 is enriched in these cells, which is known to participate in the regulation of cardiac repolarization 71,72 . NC3 and NC4 subpopulations shared a broadly similar transcriptional profile including LGR5 , a G-protein-coupled receptor involved in Wnt -signaling that promotes CM differentiation 73 and demarcates a subset of CM in the outflow tract 74 ; this region often becomes arrhythmogenic in heart disease 75 . These cells also expressed genes associated with coronary artery disease, PPP2R2B 76 , LSAMP 77 and LPL an endothelial enzyme involved transporting lipoproteins into the heart 78 .…”
Section: Nc1 Was Distinguished By Enriched Expression Ofmentioning
confidence: 99%
“…Our results showed that there existed a co-expression of vascular markers CD31 and VE-cadherin in the spheroids, suggesting that the 3D suspension culture may support both cardiac and vascular cell generation. Another study reported that downregulation of LGR5 shifts the lineage commitment of hPSCs from cardiomyocytes to endothelial cells 56 . Formation of definitive mesoderm and the cardiac mesoderm by paracrine factors was reported to depend on the size of the aggregates (indicates spatial cell density) 57 .…”
Section: Discussionmentioning
confidence: 99%